Genetic dissection of medial habenula–interpeduncular nucleus pathway function in mice - Kobayashi, Yuki; Sano, Yoshitake; Vannoni, Elisabetta; Goto, Hiromichi; Ikeda, Toshio; Suzuki, Hitomi; Oba, Atsuko; Kawasaki, Hiroaki; Kanba, Shigenobu; Lipp, Hans-Peter; Murphy, Niall P.; Wolfer, David P.; et al. (Frontiers in Behavioral Neuroscience, 2013)
The habenular complex linking forebrain and midbrain structures is subdivided into the medial (mHb) and the lateral nuclei (lHb). The mHb is characterized by the expression of specific nicotinic acetylcholine receptor isoforms and the release of acetylcholine to the interpeduncular nucleus (IPN), the sole output region of the mHb. The specific function of this circuit, however, is poorly understood. Here we generated transgenic mice in which mHb cells were selectively ablated postnatally. These lesions led to large reductions in acetylcholine levels within the IPN. The mutant mice exhibited abnormalities in a wide range of behavioral domains. They tended to be hyperactive during the early night period and were maladapted when repeatedly exposed to new environments. Mutant mice also showed a high rate of premature responses in the 5-choice serial reaction time task (5CSRTT), indicating impulsive and compulsive behavior. Additionally, mice also exhibited delay and effort aversion in a decision-making test, deficits in spatial memory, a subtle increase in anxiety levels, and attenuated sensorimotor gating. IntelliCage studies under social housing conditions confirmed hyperactivity, environmental maladaptation, and impulsive/compulsive behavior, delay discounting, deficits in long-term spatial memory, and reduced flexibility in complex learning paradigms. In 5CSRTT and adaptation tasks, systemic administration of nicotine slowed down a nose-poke reaction and enhanced adaptation in control but not mutant mice. These findings demonstrate that the mHb–IPN pathway plays a crucial role in inhibitory control and cognition-dependent executive functions.